2021
DOI: 10.1094/pdis-07-20-1593-re
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Biocontrol Strain Bacillus amyloliquefaciens FS6 for Excellent Control of Gray Mold and Seedling Diseases of Ginseng

Abstract: The biocontrol efficacy of Bacillus amyloliquefaciens FS6 against seedling diseases and gray mold of ginseng, as well as application techniques were evaluated in a series of field trials. FS6 fermentation broth showed a strong antagonistic effect against the ginseng fungal pathogens, and the inhibition rates on mycelial growth and spore germination were 84 to 88% and 71 to 72%, respectively. Field evaluation showed that combination of seed and soil treatments exhibited better protection than that of individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Biological control has been recognized as a promising and sustainable measure because of less pollution to the environment and a lower health danger compared with the chemical control. B. amyloliquefaciens with a higher antagonistic activity against phytopathogens can be successfully used as a potential biocontrol agent to control diverse crop diseases, including potato scab caused by Streptomyces griseoplanus [ 24 ]; wheat root rot caused by Bipolaris sorokiniana [ 25 ]; ginseng gray mold caused by B. cinerea [ 26 ]; alfalfa anthracnose caused by C. truncatum [ 27 ]; tomato bacterial wilt caused by Ralstonia solanacearum [ 28 ]; tomato bacterial canker caused by Clavibacter michiganensis [ 29 ]; wheat Fusarium head blight caused by F. graminearum [ 30 ]; and sugar beet leaf spot disease caused by Pseudomonas syringae pv. aptata [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological control has been recognized as a promising and sustainable measure because of less pollution to the environment and a lower health danger compared with the chemical control. B. amyloliquefaciens with a higher antagonistic activity against phytopathogens can be successfully used as a potential biocontrol agent to control diverse crop diseases, including potato scab caused by Streptomyces griseoplanus [ 24 ]; wheat root rot caused by Bipolaris sorokiniana [ 25 ]; ginseng gray mold caused by B. cinerea [ 26 ]; alfalfa anthracnose caused by C. truncatum [ 27 ]; tomato bacterial wilt caused by Ralstonia solanacearum [ 28 ]; tomato bacterial canker caused by Clavibacter michiganensis [ 29 ]; wheat Fusarium head blight caused by F. graminearum [ 30 ]; and sugar beet leaf spot disease caused by Pseudomonas syringae pv. aptata [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Scanning electron microscopy observation revealed that the hyphae of V. dahliae were destroyed to be dehydrated, distorted, dissociated and forming hollows, after fungi were treated with B. amyloliquefaciens Oj-2.16 spore suspension in panel confrontation experiments. B. amyloliquefaciens might secrete some antimicrobial substances, such as antimicrobial proteins and peptides, which can damage the mycelial structure, including deformation, expanding hyphae, and leaking protoplasm [ 26 , 41 ]. Genes involved in antifungal lipopeptide and dipeptide biosynthesis were detected in B. amyloliquefaciens strain Oj-2.16, suggesting that Oj-2.16 could produce fengycin, surfactin, iturin, and bacilysin.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure for the analysis of the inhibitory effect of different Bacillus spp. on Ggt growth was carried out according to previous reports (Zhang et al, 2014a;Wang et al, 2021). The identical amount of Ggt mycelium were inoculated in the central area of the dishes with PDA medium and the bacterial cultures (which were precultivated till OD 600 = 1.0) were inoculated on the medium 2.5 cm apart from the Ggt inoculum and subsequently incubated at 26 ā€¢ C. The experiment was repeated three times, with each containing three technical replicates.…”
Section: Screening Of Antagonists and Observation Of Ggt Myceliummentioning
confidence: 99%
“…Therefore, it is recommended to evaluate biocontrol activity initially in vitro and in vivo under laboratory conditions, followed by field trials to check the adaptability and persistence (effective duration) of biocontrol agents ( De Silva et al, 2019 ). However, reports on the evaluation of the biocontrol efficacy of microbe-based biocontrol agents under field conditions were rare, particularly on medicinal plants ( Eljounaidi et al, 2016 ; Wang et al, 2021 ). Li et al (2019 , 2020) reported that Penicillium griseofulvum CF3 and Streptomyces pactum Acy12 showed biocontrol efficacy on root diseases of A. carmichaelii .…”
Section: Introductionmentioning
confidence: 99%